2015
DOI: 10.1016/j.marmicro.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel high-pressure culture experiments on deep-sea benthic foraminifera — Evidence for methane seepage-related δ13C of Cibicides wuellerstorfi

Abstract: In field studies of active hydrocarbon seeps the carbon isotopic composition of Rose Bengal stained benthic foraminiferal tests (δ 13 C test ) and bottom water DIC (δ 13 C DIC ) deviates from their normal marine ratios. This circumstance led to ongoing discussions on whether aerobic foraminifers like Cibicides wuellerstorfi are capable of living at seepage sites and, more importantly, if their tests reflect the low δ 13 C values of emanating methane. To evaluate the discrepancy between δ 13 C DIC and δ 13 C te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…For instance, Herguera et al (2014) compared δ 13 C signatures of porewater DIC with the δ 13 C signature of living benthic foraminifera and demonstrated that methane-derived DIC from porewater is not directly incorporated during the primary biomineralization of the test. Whereas a recent publication by Wollenburg et al (2015) using novel culturing techniques resembling deep-sea conditions with injections of methane supports the idea that the uptake of methane-derived carbon during biomineralization is reflected in the test δ 13 C composition of benthic foraminifera. Despite controversial results, one explanation for slightly negative δ 13 C values of the test calcite (as low as -5.6 ‰) is that foraminifera incorporate methane-derived DIC from the ambient water during the biomineralization (Panieri et al, 2014;Panieri and Sen Gupta, 2008;Rathburn et al, 2003;Sen Gupta et al 1997).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, Herguera et al (2014) compared δ 13 C signatures of porewater DIC with the δ 13 C signature of living benthic foraminifera and demonstrated that methane-derived DIC from porewater is not directly incorporated during the primary biomineralization of the test. Whereas a recent publication by Wollenburg et al (2015) using novel culturing techniques resembling deep-sea conditions with injections of methane supports the idea that the uptake of methane-derived carbon during biomineralization is reflected in the test δ 13 C composition of benthic foraminifera. Despite controversial results, one explanation for slightly negative δ 13 C values of the test calcite (as low as -5.6 ‰) is that foraminifera incorporate methane-derived DIC from the ambient water during the biomineralization (Panieri et al, 2014;Panieri and Sen Gupta, 2008;Rathburn et al, 2003;Sen Gupta et al 1997).…”
Section: Introductionmentioning
confidence: 95%
“…Benthic foraminifers live in the dark, cold, deep ocean, at comparably stable physical environmental conditions, and, like metazoans in the same environment [ 19 ], display a high species diversity [ 20 ]. The impact of climate change on benthic deep-sea organisms is significantly less well understood than is the case for shallow water organisms, mainly because of the difficulties in collecting them from their habitat and successfully culturing them, where necessary at in situ pressures [ 21 ]. Traditionally, impacts of climate change in the fossil record have been assessed in terms of relative or absolute abundance of species, and their origination and extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, impacts of climate change in the fossil record have been assessed in terms of relative or absolute abundance of species, and their origination and extinction. Such data show that the PETM resulted in a significant extinction of benthic foraminifera [ 21 ] and a transient faunal turnover [ 22 ], as well as migration to higher latitudes in planktic species [ 23 , 24 ]. Experimentally, it has been shown that foraminifers are able to control their calcification [ 25 ] and, using novel tomographic methodologies [ 22 ], unexpectedly increased calcification during the PETM at least at some locations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…T Torres et al, 2003;Hill et al, 2004;Heinz et al, 2005;Panieri, 2006;Mackensen et al, 2006;Lobegeier and Sen Gupta, 2008;Fontanier et al, 2014a;Herguera et al, 2014;Wollenburg et al, 2015). Foraminiferal species living in cold seep ecosystems are not endemic/ exotic but are recruited from adjacent non-seep zones (e.g., Sen Gupta and Aharon, 1994;Kitazato, 1996;Sen Gupta et al, 1997;Rathburn et al, 2000Rathburn et al, , 2003Lobegeier and Sen Gupta, 2008;Fontanier et al, 2014a;Herguera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A wide array of metabolic adaptations (facultative anaerobic metabolism, mutualism with prokaryotes), habitat and food preference (elevated epibiotic habitat, bacteriovore) explain foraminiferal occurrence in methane-and sulfide-enriched sediments (e.g., Bernhard et al, 2001;Panieri, 2006;Mackensen et al, 2006;Sen Gupta et al, 2007;Lobegeier and Sen Gupta, 2008). The δ 13 C values in (living) foraminiferal tests record the seepage of methane-enriched fluid, with a clear shift (several per mil units) to lower signatures compared to adjacent non-seep areas (Sen Gupta and Aharon, 1994;Rathburn et al, 2000Rathburn et al, , 2003Hill et al, 2004;Mackensen et al, 2006;Fontanier et al, 2014a;Wollenburg et al, 2015). The lack of major δ 13 C isotopic variability recorded in living foraminiferal tests from methane-rich seep zones vs. hydrate-gas fluids, leads to the assumption that foraminifera mostly calcify during periods of low methane discharge or during intermittent episodes of seawater injection into the sediment (Torres et al, 2003;Panieri, 2006;Fontanier et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%